The study of the correlation level of cystatin-c elevation in hemodialysis patients with Toxoplasma gondii in Baquba / Diyala - Salah Salem, Maysaloon; Jassim Shaker, Mohammed; Khalid Mohammed, Nabil (Diyala Journal of Medicine, 2022)
Background: Toxoplasma gondii is the most common infection of protozoa, affecting a wide range of hosts. Toxoplasmosis is usually asymptomatic in immunocompetent persons, but in immunocompromised persons (e.g., patients on dialysis) significant problems, and may progress to a life-threatening infection. Objective: To investigate the correlation level of cystatin-C elevation in hemodialysis patients with Toxoplasma gondii in Baquba / Diyala. Patients and Methods: A group of blood samples, consisting of 75 dialysis patients and 50 healthy controls, to totaling 125 were examined for the detection of anti-toxoplasma antibodies and Cystatin-C In Baquba Teaching Hospital from November 2020 to April 2021 using Enzyme-Linked Immunosorbent assay . Results: The total numbers Of the 125 samples examined, were showed that the Mean ± SE for cystatin-c in the group of patients was 2.43 ± 0.10 higher compared to the healthy individuals 2.02 ± 0.21, The results show that correlation coefficient between Toxoplasma IgG and Cystatin-c in hemodialysis patients, where it was found that the correlation coefficient between them was 0.34. Conclusion: The level of cystatin-C in hemodialysis patients was higher compared to the control group , and found significant correlation between the rice of Cystatin-C and the presence of toxoplasma IgG in dialysis patients. Keywords: Toxoplasma gondii, Hemodialysis, Cystatin-c